Pelatihan UMKM Berbahan Dasar Daun Katuk pada Kelompok Wanita Tani (KWT) di Desa Setu Patok - Intan Fitria Mahmud; Rindang Matoati; Ajeng Widyaningrum Kusuma Wardhani; Solikhah Solikhah; Anisa Fitri; Andika Rakryan Mahardika; Fakhri Salman Mussyafa; Jennifer Natalia Christsanta; Adita Yulinda Gunawan (Universita Bangka Belitung, 2022)
The implementation of the Thematic Real Work Lecture (KKNT) which is a mandatory activity for IPB University students has been carried out on June 23, 2022 to August 2, 2022, located in Setupatok Village Mundu District, Cirebon Regency. The main objective of the KKN-T activity is to solve the stunting problem by improving lifestyle and educating the importance of 1000 HPK, and creating a sustainable food ecosystem in the form of aquaponics and maggot cages. Theimplementation of KKN-T activities is divided into three stages, namely the planning stage, preparation stage, and program implementation. The programs implemented were Penyuluhan Gizi Remaja Putri, Penyuluhan Gizi Ibu Hamil,Aquades (Aquaponik Desa) and Sop Belut (Solusi Pakan Beternak Lele Gendut), and Menanam Padi (MenumbuhkanKemandirian dan Pelatihan Digitalisasi) and Perizinan UMKM. Activities are carried out offline with materials in the form of PowerPoint or flyers, pre- and post-tests are carried out and aquaponics and maggot cages are made directly. Theresults of the Nutrition Counseling program for Young Women were an increase in nutritional knowledge by 54% of 35 MA An-Nur Setupatok students and 67% of 9 youths at the Setupatok posyandu. Setupatok Village, and the existence of examples of sustainable food ecosystems that can be continued and developed by the Setupatok Village community